Fabrication of novel carrageenan based stimuli responsive injectable hydrogels for controlled release of cephradine. Issue 22 (17th April 2019) - Rasool, Atta; Ata, Sadia; Islam, Atif; Khan, Rafi Ullah
Abstract : Kappa carrageenan was used to prepare hydrogels having novel compositions with poly(vinyl alcohol) (PVA) and a crosslinker (3-aminopropyl)triethoxysilane (APTES). Abstract : Kappa carrageenan was used to prepare hydrogels having novel compositions with poly(vinyl alcohol) (PVA) and a crosslinker (3-aminopropyl)triethoxysilane (APTES). FTIR was used to confirm the structure and composition of hydrogels. The swelling behavior of hydrogels was studied under different conditions of pH and electrolytic aqueous media. The most efficient swelling result (200%) was observed by the sample containing a low fraction of crosslinker. It also showed different swelling responses in different pH solutions that made it suitable for drug delivery. Thermogravimetric analysis (TGA) illustrated that with the increase in crosslinker amount, the stability of hydrogel was increased. The biodegradation analysis of the hydrogels exhibited the break down by various enzymes into small chain polysaccharides that further broke down in the metabolic pathways. It was revealed that all the hydrogel samples showed strong antibacterial activity against S. aureus and a little against E. coli . Cephradine was used as a model drug and its in vitro release was studied in simulated intestinal fluids (SIF). This release account of the cephradine demonstrated that the release of the drug increased as the time and pH increased, reaching its maximum amount of 85.5% after 7.5 h.